2019
DOI: 10.1213/ane.0000000000004553
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxemia Within the First 3 Postoperative Days Is Associated With Increased 1-Year Postoperative Mortality After Adjusting for Perioperative Opioids and Other Confounders

Abstract: BACKGROUND: Postoperative hypoxemia (POH) is common and primarily treated with temporary oxygen supplementation. Because the clinical impact of POH is sometimes presumed as minor, efforts to better understand and minimize it have been limited. Here, we hypothesized that, after adjusting for opioids received perioperatively and other confounders, the frequency of POH events (POH%) reported within the first 3 postoperative days (PODs) is associated with increased postoperative 1-year mortality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 27 publications
0
21
1
2
Order By: Relevance
“…Hypoxemia is one of the most adverse respiratory events in PACU, 32 which could increase 1-year postoperative mortality. 33 In our study, we did not found that wearing medical masks could reduce oxygen saturation after extubation. No more hypoxemia and SpO 2 <95% happened in these patients.…”
Section: Discussioncontrasting
confidence: 61%
“…Hypoxemia is one of the most adverse respiratory events in PACU, 32 which could increase 1-year postoperative mortality. 33 In our study, we did not found that wearing medical masks could reduce oxygen saturation after extubation. No more hypoxemia and SpO 2 <95% happened in these patients.…”
Section: Discussioncontrasting
confidence: 61%
“…However, opioids contribute to hypoxemia, and patients who received greater opioid doses were shown to be more likely to experience at least one episode of postoperative hypoxemia. 34 Postoperative opioid-induced respiratory depression has been associated with devastating consequences such as death and brain damage. 35 There are several limitations to our study.…”
Section: Opioid-free Anesthesiamentioning
confidence: 99%
“…However, even minor PPCs are clinically relevant and lead to undesirable outcomes. 33 , 34 The defined PPCs would not fail to identify a significant PPC as all moderate-to-severe PPCs should involve at least one of the defined PPCs. The IMPROVE trial 5 found that lung-protective ventilation reduced postoperative complications and LOS, and the current study revealed a reduction in postoperative complications but no reduction in LOS with the use of the OLS.…”
Section: Discussionmentioning
confidence: 99%